The learning impact native teachers have in students in the English Teaching Fellowship program inside the English Foreign Language classroom in public institutions in Armenia Quindío. (2016)
This project tends to show the learning impact the help of foreign speakers has to reinforce English level in some public institutions in Armenia, Quindío. As this is a project that has not been carried out in public institutions before, there are some expectations about it. Therefore, the aims of this research were to analyze the development of the English Teaching Fellowship Program, the pedagogical transcendence and the learning impact it has for students. It was found that the Program is pertinent but some aspects of it can be modified in order to enhance its quality